2013
DOI: 10.1021/jp410121h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ultrafast Excited-State Deactivation in Adenosine

Abstract: Recently, resonant two-photon ionization experiments on isolated adenine and adenosine suggested that adenosine exhibits a significantly shorter excited-state lifetime than adenine, which indicates the existence of an efficient excited-state deactivation mechanism in adenosine that is not existent in adenine. We report on ab initio investigations on a syn and an anti conformer of adenosine exhibiting an intramolecular O-H···N3 hydrogen bond. For both conformers, we have identified the existence of a barrierles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 36 publications
8
118
0
1
Order By: Relevance
“…The challenges stem from the multi-reference nature of CIs. [134][135][136][137] These methods can be combined with classical theories in order to include environmental effects. Such calculations employ mixed quantum and classical (QM/MM) methods, where the chromophore is treated using high level electronic structure methods, while the surroundings (e.g.…”
Section: Computational and Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges stem from the multi-reference nature of CIs. [134][135][136][137] These methods can be combined with classical theories in order to include environmental effects. Such calculations employ mixed quantum and classical (QM/MM) methods, where the chromophore is treated using high level electronic structure methods, while the surroundings (e.g.…”
Section: Computational and Theoretical Methodsmentioning
confidence: 99%
“…85,[160][161][162][163] Such oop deformation-based IC routes are also intrinsic to the DNA/RNA base pairs and isolated nucleosides, but these can also undergo IC along PCET reaction paths -which are proposed to account for the much shorter excited state lifetimes of nucleosides compared to the isolated nucleobases. 85,135,164 Within the cellular medium, strands of RNA, ADP or ATP, that contain analogous molecular moieties to that of DNA nucleobases and nucleosides, are also expected to show some degree of photostability -protecting their molecular integrity and the local environment by absorbing (and thus reducing) the incident UV flux. Nucleobases and nucleosides are generally contained well within the cellular environment, however, and are only exposed in abnormally harsh and penetrating UV-environments.…”
Section: Molecular Constituents In Natural Sunscreensmentioning
confidence: 99%
“…3 DNA bases are susceptible to protonation through proton transfer or other reaction mechanisms. 4,5 The protonation processes are important because alternative tautomeric structures of the DNA bases can be formed. The existence of such non-canonical tautomers could induce longer excited state lifetimes [1][2][3] or development of mutations in the nucleic acid replication because the Hbonding structure changes leading to failures in the recognition process.…”
Section: Introductionmentioning
confidence: 99%
“…It confirms that the energy decay of the hot charge transfer states to the ground state during the phenyl ring rotation is fully non-radiative. Although such a very fast non-radiative decay of the CT1 state to the ground state may be surprising, it could be supported by the data already reported in the literature [16,17]. It has been found that for the planar organic groups, which undergo rotation during the charge transfer, there could be a significant conical intersection or, at least avoided crossing of CT state potential energy surface with that of the ground state.…”
Section: Charge Transfer Statesmentioning
confidence: 53%